Enhancing sweetness perception with vanilla extract: Strategy for developing low-sugar food formulations for the elderly - Soontrunnarudrungsri, Aussama; Chantrapornchai, Withida; Rimkeeree, Hathairat (Agriculture and Natural Resources, 2023)
Importance of the work: Excessive sugar consumption can lead to various health problems, especially in the elderly. Vanilla extract can effectively enhance sweetness perception, enabling sugar reduction in food formulations without compromising consumer acceptability. Objectives: To investigate the effect of adding vanilla extract on the sweetness perception and acceptance of three food models (water, milk, and coconut milk) among elderly participants. Materials & Methods: A multi-sensory integration approach was used to reduce the sugar content in three food models. Initially, the sugar content in each model was set based on commercial products and gradually reduced in 0.5% increments, resulting in seven sugar levels. Vanilla extract was added to all samples. Trained panelists evaluated the flavor profiles of the three food models with and without vanilla extract. Elderly consumers assessed the sweetness perception and overall liking of the models. Results: Vanilla extract enhanced the sweetness perception in all three models. In the water models, vanilla enabled a 15% reduction in sugar without compromising the perceived sweet aroma or sweetness. In the coconut milk models, a 13.33% reduction in coconut sugar was achieved while maintaining the perceived sweet aroma and sweetness. However, in the milk models, the reduced-sugar formulation with vanilla was less sweet than the control, although the sweet aroma was not affected. For elderly consumers, vanilla enabled a sugar reduction in all three food models without affecting overall liking. Main finding: Vanilla extract could effectively enhance sweetness perception in various food models, enabling a reduction in sugar content without compromising palatability and overall consumer acceptance. This strategy could be a promising approach to product reformulation without relying on non-nutritive sweeteners.